2016
DOI: 10.18632/oncotarget.8018
|View full text |Cite
|
Sign up to set email alerts
|

EphA8 is a prognostic marker for epithelial ovarian cancer

Abstract: EphA8 is one of the Eph receptors in the Eph/ephrin receptor tyrosine kinase (RTK) subfamily. During tumorigenesis, EphA8 is involved in angiogenesis, cell adhesion and migration. In this study, we determined the mRNA and protein expression levels of EphA8 in cancerous and normal ovarian tissue samples by quantitative reverse transcription PCR (qRT-PCR) (N = 60) and tissue microarray immunohistochemistry analysis (TMA-IHC) (N = 223) respectively. EphA8 protein levels in cancer tissues were correlated with epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
1
19
0
1
Order By: Relevance
“…Patients only diagnosed as either TNM stage II or stage III OTSCC were enrolled in our study, for, on one hand, there is a very limited number of patients who were diagnosed as OTSCC at very early stage (stage I); on the other hand, patients at TNM stage IV have a very poor prognosis, making it hard to conduct a follow-up study. By examining the mRNA levels of EphA8 in fresh OTSCC tissues and adjacent non-tumor tissues, we found that EphA8 was highly expressed in OTSCC tissues comparing with non-tumor tissues, which was consistent with findings from an epithelial ovarian cancer study [ 20 ]. Furthermore, we also detected the differential expressions of EphA8 in different stages of OTSCC by performing IHC staining.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Patients only diagnosed as either TNM stage II or stage III OTSCC were enrolled in our study, for, on one hand, there is a very limited number of patients who were diagnosed as OTSCC at very early stage (stage I); on the other hand, patients at TNM stage IV have a very poor prognosis, making it hard to conduct a follow-up study. By examining the mRNA levels of EphA8 in fresh OTSCC tissues and adjacent non-tumor tissues, we found that EphA8 was highly expressed in OTSCC tissues comparing with non-tumor tissues, which was consistent with findings from an epithelial ovarian cancer study [ 20 ]. Furthermore, we also detected the differential expressions of EphA8 in different stages of OTSCC by performing IHC staining.…”
Section: Discussionsupporting
confidence: 87%
“…Ephs are the largest subfamily of RTKs and have been showed to be implicated in many aspects of cancer [ 28 , 29 ]. In this study, we focused on one of the receptors in the Ephs RTKs subfamily, EphA8, which has been reported to be pivotal in epithelial ovarian cancer [ 20 ]. In order to figure out the potential effects of EphA8 in OTSCC, we enrolled a total of 119 OTSCC patients and performed a retrospective study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the role of EPHA8 in cancer stem cells remains elusive, its overexpression correlates to a poor overall survival in other human malignancies, such as epithelial ovarian cancer (EOC) (24)(25)(26). In EOC, both EPHA8 and ephrin-A5 are significantly up-regulated (24), while only EPHA8 was reported to be overexpressed in OTSCC and GC (25).…”
Section: Discussionmentioning
confidence: 99%